Autologous Micrografts from Scalp Tissue: Trichoscopic and Long-Term Clinical Evaluation in Male and Female Androgenetic Alopecia. (28th January 2020) - Gentile, Pietro; Scioli, Maria Giovanna; Cervelli, Valerio; Orlandi, Augusto; Garcovich, Simone
Abstract : Tissue engineering in hair regrowth aims to develop innovative and not-invasive procedures to advance the hair regrowth. A placebo-controlled, randomized, evaluator-blinded, half-head group study to compare hair regrowth with micrografts containing human hair follicle mesenchymal stem cells (HF-MSCs) vs. placebo was reported. After 58 weeks, 27 patients displayed in the targeted area an increase of hair count and hair density, respectively, of 18.0 hairs per 0.65 cm 2 and 23.3 hairs per cm 2 compared with baseline, while the control area displayed a mean decrease of 1.1 hairs per 0.65 cm 2 and 0.7 hairs per cm 2 (control vs. treatment: P < 0.0001 ). After 26 months, 6 patients revealed dynamic hair loss and were retreated. More broad controlled examinations are required. HF-MSCs contained in micrografts may represent a safe and viable treatment alternative against hair loss.